Acute morphine activates satellite glial cells and up-regulates IL-1β in dorsal root ganglia in mice via matrix metalloprotease-9 - Berta Temugin; Liu Tong; Liu Yen-Chin; Xu Zhen-Zhong; Ji Ru-Rong (SAGE Publishing, 2012)
Abstract Background Activation of spinal cord glial cells such as microglia and astrocytes has been shown to regulate chronic opioid-induced antinociceptive tolerance and hyperalgesia, due to spinal up-regulation of the proinflammatory cytokines such as interleukin-1 beta (IL-1β). Matrix metalloprotease-9 (MMP-9) has been implicated in IL-1β activation in neuropathic pain. However, it is unclear whether acute opioid treatment can activate glial cells in the peripheral nervous system. We examined acute morphine-induced activation of satellite glial cells (SGCs) and up-regulation of IL-1β in dorsal root ganglia (DRGs), and further investigated the involvement of MMP-9 in these opioid-induced peripheral changes. Results Subcutaneous morphine injection (10 mg/kg) induced robust peripheral glial responses, as evidenced by increased GFAP expression in DRGs but not in spinal cords. The acute morphine-induced GFAP expression is transient, peaking at 2 h and declining after 3 h. Acute morphine treatment also increased IL-1β immunoreactivity in SGCs and IL-1β activation in DRGs. MMP-9 and GFAP are expressed in DRG neurons and SGCs, respectively. Confocal analysis revealed a close proximity of MMP-9 and GFAP immunostaining. Importantly, morphine-induced DRG up-regulation of GFAP expression and IL-1β activation was abolished after Mmp9 deletion or naloxone pre-treatment. Finally, intrathecal injections of IL-1β-selective siRNA not only reduced DRG IL-1β expression but also prolonged acute morphine-induced analgesia. Conclusions Acute morphine induces opioid receptors- and MMP-9-dependent up-regulation of GFAP expression and IL-1β activation in SGCs of DRGs. MMP-9 could mask and shorten morphine analgesia via peripheral neuron-glial interactions. Targeting peripheral glial activation might prolong acute opioid analgesia.